Peran E-HRM dalam Meningkatkan Praktik Green HRM: Studi tentang Kinerja Organisasi Berkelanjutan di Era Digital - Yoki Muchsam; Galih Respati; Mulfi Sandi Yuda; Mochamad Afrizal Maulana (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Digital transformation and sustainability demands are driving the need for the integration of E-HRM and Green HRM to achieve sustainable organizational performance. This integration serves as a solution to the challenges of resource efficiency, carbon footprint reduction, and enhanced employee engagement in the digital era. This research aims to analyse the role of E-HRM in enhancing Green HRM practices and its impact on sustainable organizational performance. The research methodology employs a Systematic Literature Review (SLR), utilising the Scopus database, with selection based on inclusion-exclusion criteria, data extraction, and thematic analysis of selected journals. The anticipated impact of E-HRM is its support for Green HRM through the digitalization of HR processes that reduce resource usage, the establishment of digital platforms for environmental awareness, and data-driven impact measurement. The integration of both significantly enhances sustainable performance across three dimensions: environmental (a 20-30% reduction in carbon footprint), economic (15-25% cost savings), and social (30-40% increase in employee engagement). Key implementation factors include technological readiness, management commitment, and alignment with ESG strategies. This research contributes a conceptual framework for the integration of E-HRM and Green HRM, along with practical recommendations for achieving sustainable competitive advantage in the digital age.